Identification of Critical Waste in Lean Hospital Administration Through Bibliometric Study - Cahya, Sartika Pradhipta; Sundari, Sri (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Lean principles, originating from the manufacturing sector, have gained traction in healthcare as hospitals aim to enhance operational efficiency and service quality. Specific background: Despite growing interest, the application of Lean in hospital settings remains fragmented, particularly concerning waste identification and management. Knowledge gap: Few studies provide a comprehensive mapping of research trends and critical issues in Lean Hospital literature related to waste. Aim: This study aims to bridge that gap by conducting a bibliometric analysis to identify and classify critical research streams addressing waste in Lean Hospital administration. Results: Analyzing 97 peer-reviewed articles using R Studio and VOSviewer, we identified five key research streams: (1) Lean Hospital and Waste Reduction, (2) Healthcare Quality Improvement, (3) Digital Transformation, (4) Policy Implementation, and (5) Sustainability. Novelty: This study offers a systematic synthesis of two decades of scholarly work, presenting a structured overview of evolving themes and proposing future research questions within each stream. Implications: The findings advance academic understanding by categorizing existing literature and guiding future research on Lean healthcare, particularly in waste reduction, ultimately supporting evidence-based administrative improvements in hospital management. Highlights: Identifies five core research streams in Lean Hospital literature. Uses bibliometric analysis over a 20-year span. Proposes future research directions for each stream. Keywords: Lean Hospital, Waste Reduction, Healthcare Quality, Digital Transformation, Sustainability